Translation in the digital age - Cronin, Michael, 1960- (New perspectives in translation studies., 2013)
Translation is living through a period of revolutionary upheaval. The effects of digital technology and the internet on translation are continuous, widespread and profound. From automatic online translation services to the rise of crowdsourced translation and the proliferation of translation Apps for smartphones, the translation revolution is everywhere. The implications for human languages, cultures and society of this revolution are radical and far-reaching. In the Information Age that is the Translation Age, new ways of talking and thinking about translation which take full account of the dramatic changes in the digital sphere are urgently required. Michael Cronin examines the role of translation with regard to the debates around emerging digital technologies and analyses their social, cultural and political consequences, guiding readers through the beginnings of translation's engagement with technology, and through to the key issues that exist today.